Oferta de escolas e retorno do ensino médio entre os jovens no Brasil - Franca, Maíra Penna,Machado, Danielle Carusi,Corseuil, Carlos Henrique (Instituto de Pesquisa Econômica Aplicada, 2022)
Schooling attendance improved significantly in Brazil, mainly for primary schooling. Attendance levels however are still deficient at secondary level; where dropout levels also worries policy makers. This paper aims to estimate the wage premium for secondary education attained by young workers aged 20 to 24 in Brazil; as this could potentially lead to low levels of interest for attending secondary schools. We take into account the endogeneity of education in the wage equation, by employing a set of instruments that capture the supply density of schools in the municipality when the young worker was 15 years old; considered as the entry age for secondary school. The return estimates obtained by the method of instrumental variables ranged from 11% to 20%. The results also indicate that measures of school supply have a positive and significant relationship with the probability of a young person having completed high school.
10.38116/td2804
Keywords: Graue Literatur; economic returns; high school education; instrumental variables; human capital